2012
DOI: 10.1270/jsbbs.61.593
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and population structure of black soybean landraces originating from Tanba and neighboring regions

Abstract: Black soybean landraces that had been cultivated in Tanba region and the neighboring regions and conserved black soybean landraces, including those from other regions in Japan, were used in this study. The polymorphisms of 78 SSR markers in nuclear DNA and 6 SSRs in chloroplast DNA were analyzed in the black soybean landrace populations. The result of phylogenic analysis revealed that the black soybeans can be classified into six clades. The landraces originating from Tanba region were classed into first and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…A previous study on revolutionary relationship between Glycine soja and Glycine max revealed two clusters (Wen et al, 2009). The results of the present study are consistent with the findings of Wang et al (2006), Wen et al (2008), Hirota et al (2012), Ghosh et al (2014), and Bisen et al (2015). The genotypes used in this study showed genetic variation because of the different source and/or area from which they were collected; hence, they belonged to different clusters.…”
Section: Introductionsupporting
confidence: 91%
“…A previous study on revolutionary relationship between Glycine soja and Glycine max revealed two clusters (Wen et al, 2009). The results of the present study are consistent with the findings of Wang et al (2006), Wen et al (2008), Hirota et al (2012), Ghosh et al (2014), and Bisen et al (2015). The genotypes used in this study showed genetic variation because of the different source and/or area from which they were collected; hence, they belonged to different clusters.…”
Section: Introductionsupporting
confidence: 91%
“…The hybridization origin of the semi-wild soybean has been proposed [13] , [60] . However, direct evidence in support of this hypothesis is lacking, although hybridization events between cultivated and wild soybean have been observed in natural field conditions [6] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Among all the genotypes SL781 and SEL7 exhibited maximum (0.118g) and minimum (0.055g) weight/ seed. A wide variation for 100 seed weight has been reported by various authors among soybean seeds varying in seed coat colour (Zhang et al, 2010;Hirota et al, 2012;Goyal et al, 2012;Sharma et al, 2014 green and yellow coloured groups of soybean genotypes, respectively (Fig 1). Among black coloured soybean genotypes, dry matter was highest in SL783 and lowest in SEL37.…”
Section: Resultsmentioning
confidence: 82%